An integrated approach to grassland productivity modelling using spectral mixture analysis, primary production and Google Earth Engine - Vermeulen, Liezl Mari (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.